University management: Technology for monitoring the reputation of an educational brand - T. D. Sinyavets; E. A. Luneva; N. V. Katunina (Образование и наука)
Introduction. The processes of formation of a multipolar world lead to changes in higher education. An important consequence of the ongoing changes is the reorientation of the activities of universities to the domestic market, the development of new educational programmes, and learning technologies. Against the background of growing competition in this direction, the reputation of an educational institution is acquiring an increasing importance in the eyes of various stakeholders.Aim. The present research aimed to develop a technology for monitoring the reputation of an educational brand based on the opinions of stakeholders. The obtained technology, resulting from the analysis and generalisation of scientific works, was tested in Dostoevsky Omsk State University.Methodology and research methods. The scientific basis of the research was the methodology of brand management, formed within the framework of the marketing approach to the organisation activities, and the cognitive methodology of research was applied. The authors used the following research methods: the analysis of the external environment, the cognitive methodology of knowledge networks research (ISM analysis), the structural matrix of the interaction of factors (SSIM), and focus groups with representatives of target groups of the public that determine the reputation of an educational brand.Results. The authors developed the technology for monitoring the reputation of an educational brand. The technology includes: the structural characteristics of the research object; the selected and justified form of control of the managed object; the identified stakeholders of the educational institution; and the described procedure for monitoring the reputation of an educational brand. The key result of the study is that the proposed monitoring technology has a complex nature of analysing the influence of environmental factors on the reputation of the university brand, which allows building a hierarchy of environmental factors, as well as choosing the most effective behaviour strategy in relation to strengthening the reputation of the university in a timely manner. Scientific novelty.The scientific novelty lies in the development of up-to-date technology for monitoring the reputation of an educational brand, which is available for implementation for any higher school in Russia in terms of labour intensity and financial costs.Practical significance. The presence of a pool of strategies tied to the results of the implementation of monitoring technology allows communication activities of an educational institution to be immediately adjusted, strengthening its reputation in the market environment.